Proximal fibular osteochondroma causing splitting of common peroneal nerve leading to neuropathy in an adult – a rare case report - Ujjwal G. Wankhade; Amit Kale; Prafful Rawate; Gaurav Bathala (International Journal of Medical Research and Review, 2016)
Osteochondroma is the most common benign primary tumor of appendicular skeleton arising from the metaphyseal or metadiaphyseal region of long bones and are most commonly seen around the knee. A proximal fibular osteochondroma may distort the normal anatomical course of nerves and it may lead to vascular compression syndromes or peroneal nerve paralysis. We report a case of proximal fibular osteochondroma causing splitting of common peroneal nerve leading to neuropathy in an adult. Our article concludes that osteochondroma of proximal fibula could be responsible for common peroneal nerve palsy due to compression or entrapment and in such cases decompression of nerve should not be delayed. Moreover, we also report that osteochondroma causing splitting of midsubstance of common peroneal nerve which may surprise surgeon intraoperatively. Through this case report, we are hoping to alert surgeons that this problem may occur, and care should be taken to identify the entire common peroneal nerve prior to removal of the osteochondroma.